Subway and Skyway System: Sustainable Infrastructure for Walking? - Papa, Enrica (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The paper focuses on a peculiar typology of walking infrastructure: pedestrian subway/skyway systems. These infrastructure for the pedestrian mobility are Climate Controlled Walkway [CCW] networks made by pedestrian bridges or tunnels linking buildings, which allow pedestrians to move without using city streets and offer advantages to urban pedestrians. Prominent examples are the tunnel systems of Montreal and Toronto, the mixed tunnel/skywalk systems of Houston and Dallas, the skywalk systems of Minneapolis, Calgary and Cincinnati. The paper report some result of a comparative analysis of 19 study cases and define the main characteristic subways and skyways system where the pedestrian flows are completely separated from the vehicular traffic. The strengths are mainly related to the protection to pedestrian from weather and crime, the separation from vehicle traffic, the retails attractiveness in central business district,the reduction of car use in central areas, low maintenance costs for public authority. The weaknesses are low quality of street life, private management of the spaces and lack of orientation in the pedestrian network. Despite the success of some study cases, is still necessary to ask if these kind of pedestrian network are a sustainable solution for walking in city areas and what is the role of urban and transportation planning in order to minimize the negative effects of these practices.